solve (y-xz)p+(yz-x)q=(x+y)(x-y)
Given, "(y-xz)p+(yz-x)q = (x+y)(x-y)".
"\\Rightarrow(y-xz)p+(yz-x)q = x^2-y^2"
This equation is of the form "Pp+Qq=R" (Lagrange's linear partial differential equation).
Here, "P = y-xz, Q=yz-x, R = x^{2}-y^{2}".
The subsidiary equations are
"\\dfrac{dx}{P}=\\dfrac{dy}{Q}=\\dfrac{dz}{R}\\\\\n\\dfrac{dx}{y-xz}=\\dfrac{dy}{yz-x}=\\dfrac{dz}{x^{2}-y^{2}}~~~~~~~~~~~-(1)".
Each ratio of (1) is equal to "\\dfrac{xdx+ydy}{(y^{2}-x^{2})z} = \\dfrac{dx+dy}{(1+z)(y-x)}".
Let us consider,
"\\dfrac{xdx+ydy}{(y^{2}-x^{2})z} = \\dfrac{dz}{x^{2}-y^{2}}\\\\\\Rightarrow\nxdx+ydy+zdz=0\\\\\n\\text{Integrating, }\\\\ \\int xdx + \\int ydy + \\int zdz=0\\\\\\Rightarrow\n\\dfrac{x^{2}}{2}+\\dfrac{y^{2}}{2} +\\dfrac{z^{2}}{2}=\\dfrac{c_{1}}{2}\\\\\\;\\\\\\Rightarrow\nx^{2}+y^{2}+z^{2}=c_{1}"
Consider,
"\\dfrac{dx+dy}{(1+z)(y-x)}=\\dfrac{dz}{(x+y)(x-y)}\\\\\\Rightarrow\n\\dfrac{dx+dy}{1+z}=\\dfrac{dz}{-(x+y)}\\\\\\Rightarrow\n-(x+y)d(x+y)=(1+z)dz\\\\\n\\text{Integrating,}\\\\\n-\\int (x+y)d(x+y)=\\int (1+z)dz\\\\\\Rightarrow\n-\\dfrac{(x+y)^2}{2}=\\dfrac{(1+z)^{2}}{2}-\\dfrac{c_{2}}{2}\\\\\\;\\\\\n\\Rightarrow\n(1+z)^{2}+(x+y)^{2}=c_{2}"
The general solution is,
"\\phi(c_{1},c_{2})=0\\\\\n\\phi\\left(x^{2}+y^{2}+z^{2},\\left((1+z)^{2}+(x+y)^{2}\\right)\\right)=0."
Comments
Leave a comment